Antibiotic Resistance and RAPD-PCR Genotyping of Pseudomonas aeruginosa Clinical Strains Isolated from Intensive Care Unit Patients - Ghazi, Mona; Goudarzi, Hossein; Dadashi, Masoud; Taghizadeh Maleki, Donya; Abedi Ilkhichi, Parisa; Goudarzi, Mehdi; Bahramian, Aghil; Yadegarynia, Davood; Yadegar, Abbas (Novelty in Biomedicine, 2021)
Background: Pseudomonas aeruginosa is one the most important nosocomial pathogens, especially in immunocompromised patients. Identifying the source of contamination in health centers plays an important role in the control of hospital infections. The aim of this study was to determine antibiotic susceptibility and genetic patterns of P. aeruginosa isolated from patients hospitalized in intensive care unit of Masih Daneshvari Hospital, Tehran, Iran. Materials and Methods: Antibiotic susceptibility of the isolates was examined through 10 antibiotics recommended by Clinical and Laboratory Standards Institute (CLSI, 2018) guidelines using the Kirby-Bauer disc diffusion method. Random amplified polymorphic DNA (RAPD) analysis with the short primer of 272 was used to evaluate genetic relationship among the isolates and the results were analyzed by Gelcompar II software. Results: Of the antibiotics used, the most sensitive was found in colistin (96.4%) and the highest resistance rates were observed in cefotaxime (94.6%), chloramphenicol (83.9%) and imipenem (71.4%). DNA fingerprinting was able to identify 12 genetic patterns by RAPD-PCR technique. Conclusion: Antibiotic resistance in isolates of P. aeruginosa is rising and there is possibility of occurring outbreaks in the medical centers. Different sources of strains show their constant exchange via intra- and extra-hospital transmission routes. Thus, according to the data of this study, there is a serious need to control sources of infections by physicians and staff when they are working in several sectors to control and prevent the transmission of the bacterium.